PENEKANAN DAN APLIKASI AJARAN TRI KAYA PARISUDHA DALAM KEHIDUPAN KESEHARIAN DALAM MEMINIMALISIR KENAKALAN REMAJA DI ERA 4.0 - I G Agung Jaya Suryawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Juvenile delinquency becomes a matter of concern and more attention because as a child develops, it is natural for a teenager to commit a delinquency. As long as delinquency is still at a reasonable level. Therefore the role of parents in educating a child let alone adolescents is very necessary instilling values, and norms given early can affect attitudes, mental behavior of a child to be able to sort out which things need to be emulated, and which things are not worth emulating. Tri Kaya Parisudha which is the focus of this discussion is one of the Hindu Teachings to do good (subha karma). Etymologically Tri Kaya Parisudha (Sanskrit) from the word Tri means three. Kaya means actions / behavior and pansudha means (very) purified. Hierarchically starts from good thoughts and righteous words and deeds will flow.